Upaya Guru Dalam Meningkatkan Kedisiplinan Anak Usia Dini di TK IT Az Zahra Kecamatan Tuah Madani - Yenda Puspita; Dedi Ahmadi (Jurnal Pendidikan Tuntas, 2024)
As students at the age of 3 - 6 years, children begin to obey the demands or rules of their parents and social environment. dressing neatly, tidying up toys that have been used, washing hands before and after eating, storing shoes on a shoe rack, throwing garbage in its place. As in the Az Zahra IT Kindergarten, Tuah Madani sub-district, the habit of using productive time by students is seen to be lacking, lack of compliance with school rules, such as not being able to put toys back in order after use, not being orderly in washing hands, when taking shoes on the shoe rack is not neat, not making a habit of queuing, therefore it is necessary for the teacher's efforts to minimize the lack of discipline of students, thus the author formulates the title of how the teacher's efforts in improving early childhood discipline at Az Zahra IT Kindergarten, Tuah Madani Subdistrict, 2022/2023 school year. The purpose of this study was to determine how the teacher's efforts to improve early childhood discipline in the Az Zahra IT Kindergarten Tuah Madani, while the method used is a descriptive qualitative case study approach with Primary subjects include teachers and children and secondary subjects include principals and guardians of IT Az Zahra Kindergarten students in Tuah Madani District, The method of data collection that the author uses is observation, interviews, documentation, then to analyze the results of the research the author draws conclusions by inductive thinking. By using this analysis, the researcher suggests the results of the study that improving early childhood discipline in kindergarten is generally of sufficient value. Based on the results of the previous analysis and discussion, the researcher can conclude that as a teacher in improving children's discipline has a target or initiative that an increase in children's discipline through teacher efforts is expected to improve children's discipline in accordance with the 7 indicators to be developed. Through various methods and efforts, it is hoped that it will become an intermediary in improving early childhood discipline so that the education provided to children can be more optimal. Keywords: Teacher Efforts, Early Childhood Discipline, Case Study